Peace through health: traditional medicine meditation in the prevention of collective stress, violence, and war - Schneider, Robert H.; Dillbeck, Michael C.; Yeola, Gunvant; Nader, Tony (Frontiers in Public Health, 2024)
In the midst of global armed conflicts, notably the Israel-Hamas and Ukraine-Russia wars, there is an urgent need for innovative public health strategies in peacebuilding. The devastating impact of wars, including mortality, injury, disease, and the diversion of healthcare resources, necessitates effective and durable interventions. This perspective aligns with WHO recommendations and examines the role of evidence-based meditation from Ayurveda and Yoga in public health to mitigate collective stress and prevent collective violence and war. It highlights the Transcendental Meditation program, recognized for reducing stress, with contemporary evidence supporting its effectiveness in mental health, mind–body disorders, cardiovascular disease, and public health. Empirical studies with cross-cultural replications indicate that these Traditional Medicine meditation practices can reduce collective stress and prevent collective violence and war activity while improving quality of life. The mechanisms of group meditation in mitigating collective violence are explored through public health models, cognitive neuroscience, population neuroscience, quantum physics principles, and systems medicine. This perspective suggests that Transcendental Meditation and the advanced TM-Sidhi program, as a component of Traditional Medicine, can provide a valuable platform for enhancing societal well-being and peace by addressing brain-based factors fundamental to collective stress and violence.